An analysis of the discovery approach as applied to population education in Leyte - Tan, Amparo Militante 1917- (1975)
The aim of the study is to investigate the application of the discovery approach to population education in Leyte. The descriptive survey is used in the study as the principal instrument in gathering the necessary data. Data gathered was analyzed through the use of frequency counts, percentage and rank order of each item.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Vita.
Keywords: Population -- Study and teaching -- Philippines -- Leyte; Learning by discovery